The Effect Of The Hammam And Sauna On Accelerating The Recovery Process Of Young Algerian Footballers - Azedine, Didani; Cherif Mustapha, Bourenane (Journal of Sport Science Technology and Physical Activities, 2025)
The Object of the study aims to identify the impact of the hammam and sauna on accelerating the recovery process in young Algerian footballers, for this purpose, we used an empirical method. On a sample composed of 47 U19 soccer players from RC Kouba, NA Hussein Day and ES Benaknoun Chosen non-randomly, and for data collection, we used a TQR questionnaire. After collecting the results and having treated them statistically, we conclude that there are significant differences. On this basis, the study recommended the use of the sauna as a means of recovery